2022
DOI: 10.1186/s40478-022-01313-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils predominate the immune signature of cerebral thrombi in COVID-19 stroke patients

Abstract: Coronavirus disease 2019 (COVID-19) is associated with an increased risk of thrombotic events. Ischemic stroke in COVID-19 patients entails high severity and mortality rates. Here we aimed to analyze cerebral thrombi of COVID-19 patients with large vessel occlusion (LVO) acute ischemic stroke to expose molecular evidence for SARS-CoV-2 in the thrombus and to unravel any peculiar immune-thrombotic features. We conducted a systematic pathological analysis of cerebral thrombi retrieved by endovascular thrombectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…Meanwhile, it was repeatedly shown that cerebral thrombi contain NETs ( 73 , 74 ) and it was speculated that mechanisms of immunothrombosis may be crucial in the pathophysiology of cryptogenic stroke. However, like in this work, the burden of NETs in thrombi of unclear origin did not substantially differ compared to clear stroke etiologies ( 75 , 76 ).…”
Section: Discussionsupporting
confidence: 67%
“…Meanwhile, it was repeatedly shown that cerebral thrombi contain NETs ( 73 , 74 ) and it was speculated that mechanisms of immunothrombosis may be crucial in the pathophysiology of cryptogenic stroke. However, like in this work, the burden of NETs in thrombi of unclear origin did not substantially differ compared to clear stroke etiologies ( 75 , 76 ).…”
Section: Discussionsupporting
confidence: 67%
“…Microthrombi, rich in platelets, fibrin and granulocytes, were found in the vessels of lung, the kidneys, and the heart ( 163 ). Cerebral thrombi from COVID-19 patients with large vessel occlusion acute ischemic stroke show increased neutrophil infiltration ( 164 ). Curiously, despite an increase in neutrophils in the thrombi, no differences in the composition of thrombi, especially regarding NETs, between COVID-19 and control stroke patients were found ( 164 ), suggesting that neutrophils may induce immunothrombosis not exclusively via NET formation, or that other yet unidentified factors contribute to the thrombotic dysregulation.…”
Section: The Pathophysiological Influence Of Platelet-net Interplay I...mentioning
confidence: 99%
“…Cerebral thrombi from COVID-19 patients with large vessel occlusion acute ischemic stroke show increased neutrophil infiltration ( 164 ). Curiously, despite an increase in neutrophils in the thrombi, no differences in the composition of thrombi, especially regarding NETs, between COVID-19 and control stroke patients were found ( 164 ), suggesting that neutrophils may induce immunothrombosis not exclusively via NET formation, or that other yet unidentified factors contribute to the thrombotic dysregulation. Interestingly, LDGs, which are associated with autoimmune diseases and shown to cast NETs more frequently than “normal density” granulocytes, were found in COVID-19 patients ( 165 ).…”
Section: The Pathophysiological Influence Of Platelet-net Interplay I...mentioning
confidence: 99%
“…This may be because basic diseases, such as hyperlipidemia and hyperglycemia, stimulate hematopoietic cells in the bone marrow to produce a large number of white blood cells in the circulating blood ( Stumvoll et al, 2005 ; Zhou et al, 2016 ; Vekic et al, 2019 ). Neutrophils are closely related to thrombosis in IS patients with COVID-19 ( Genchi et al, 2022 ). Neutrophils account for the majority of leukocytes in IS thrombi, followed by macrophages and T cells ( Heo et al, 2020 ).…”
Section: Pathogenesis Of Ischemic Strokementioning
confidence: 99%